Mechanism for the formation of the local self-government budget and the sources of its income - Arynova, Z.A.; Tursynkhanov, D.Zh.; Nurgalieva, S.Zh. (KU Publ., 2021)
Object: to determine the main directions of strengthening the financial base of local self-government in modern conditions in the framework of the implementation of national policies in the field of socio-economic development of territories. Methods: The scientific abstraction method supported with information analysis and grouping. Findings: The results of the analysis of the main characteristics of budgets of the fourth level and the proposed ways to strengthen the revenue base of local self-government contribute to the improvement of the theory of the budget process and inter-budget relations, as well as the development of methodological foundations for the formation of local budgets. The main factor limiting the independence of local governments in the formation of the local budget is the high level of concentration of the country's income (tax) potential at the stage of its primary distribution due to the model of budget-redistributive relations used. Conclusions: By analyzing the problems of the fourth-level budgets, the directions of strengthening the financial base of local self-government were identified, the main of which are increasing the interest of rural districts in building revenue potential, improving medium-term planning, introducing progressive forms and methods of managing local finances.
Жергілікті өзін-өзі басқару бюджетін қалыптастыру механизмі жəне олардың кіріс көздері
Механизм формирования бюджета местного самоуправления и источников доходов
Keywords: budget; budget system; taxes; local budget; local self-government; rural district; national income